Strategy for Neutralizing Sustainable Oil Spills on Coastal and Small Islands in Riau Archipelago Province - A. Hadian Pratama Hamzah; Nurhasanah; Cicik Suriani; Lina Warlina; Sri Harijati (Postgraduate, University of Mataram, 2023)
Indonesia is one of the largest oil producing countries in the world. Indonesia is recorded to have produced 279.07 million barrels of oil in 2021. Indonesia's geographical location is in a strategic area which is located between the Middle East countries as oil producers and developed countries that consume oil. The Malacca Strait, which is adjacent to the Riau Islands Province as a ship transportation area, even 27% of oil spread throughout the world passes through it. In addition to economic benefits, this sea area is also at risk of oil spills which result in pollution of sea waters. The research method used in this research is literature review. The research focuses on the interior of the coast and small islands in the Riau Archipelago. The research aims to provide a collaborative strategy through sustainable oil spill management policies on coasts and small islands in the Riau Archipelago Province. The results of the research show that strategies that can be applied are socialization regarding the importance of protecting marine waters from pollution and patrolling areas that are prone to being dumps of oil. The vastness of the waters in the Riau Islands requires patrols to coordinate with BAKAMLA, Navy, Aired Police, Customs and Excise and the community. The team for handling oil in the sea of Riau Islands Province that has been formed needs to increase environmental knowledge and deepen understanding related to technology through continuous training. Operational techniques for handling oil spills must be made regular so that it is easier to concentrate and coordinate the handling of oil spills.